2023
DOI: 10.1038/s41467-023-37632-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting neuronal lysosomal dysfunction caused by β-glucocerebrosidase deficiency with an enzyme-based brain shuttle construct

Abstract: Mutations in glucocerebrosidase cause the lysosomal storage disorder Gaucher’s disease and are the most common risk factor for Parkinson’s disease. Therapies to restore the enzyme’s function in the brain hold great promise for treating the neurological implications. Thus, we developed blood-brain barrier penetrant therapeutic molecules by fusing transferrin receptor-binding moieties to β-glucocerebrosidase (referred to as GCase-BS). We demonstrate that these fusion proteins show significantly increased uptake … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Recognizing that increasing lysosomal GCase activity is a therapeutic strategy being widely pursued, we set out to determine whether LysoFix‐GBA was suitable for measuring increases in lysosomal GCase activity within cells. Delivery of recombinant enzyme to GBA1 KO cells by addition to the media, led to a transient increase in lysosomal GCase activity (Figure 3D, E) at 24 h, which diminishes over time as the enzyme is secreted from the cells into the media as the enzyme is unstable in neutral media [47] . We next showed that pharmacological perturbations to trafficking of GCase from the ER to lysosomes, induced by the known small molecules brefeldin A and monensin, [48,49] lead to a decrease in lysosomal GCase activity as measured using LysoFix‐GBA (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Recognizing that increasing lysosomal GCase activity is a therapeutic strategy being widely pursued, we set out to determine whether LysoFix‐GBA was suitable for measuring increases in lysosomal GCase activity within cells. Delivery of recombinant enzyme to GBA1 KO cells by addition to the media, led to a transient increase in lysosomal GCase activity (Figure 3D, E) at 24 h, which diminishes over time as the enzyme is secreted from the cells into the media as the enzyme is unstable in neutral media [47] . We next showed that pharmacological perturbations to trafficking of GCase from the ER to lysosomes, induced by the known small molecules brefeldin A and monensin, [48,49] lead to a decrease in lysosomal GCase activity as measured using LysoFix‐GBA (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…The senescence inducer S100A9, which is upregulated with age (Swindell et al., 2013 ), also co‐localizes and co‐aggregates with α‐SYN in 20% of Lewy bodies and 77% of neuronal cells in the substantia nigra of PD patients (Horvath et al., 2018 ). Additionally, GBA‐KO cells that exhibit elevated GluCer levels demonstrate upregulation of S100A9 (Gehrlein et al., 2023 ). This is noteworthy since S100A9 is implicated in the induction of cellular senescence (Shi et al., 2019 ) and is significantly upregulated in multiple aging murine and human tissues, including those in the central nervous system (Swindell et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%